Case Report: A Cluster of Complications During Carotid Artery Stenting Managed With Peripheral, Coronary, and Imaging Techniques - Montorsi, Piero; Galli, Stefano; Teruzzi, Giovanni; Troiano, Sarah; Caputi, Luigi; Gili, Sebastiano; Trabattoni, Daniela (Frontiers in Cardiovascular Medicine, 2021)
We describe the case of a 72 year-old-man with a severe, asymptomatic in-stent restenosis detected 4 years after index CAS. The patient was deemed at low risk and scheduled for re-angioplasty with drug-coated-balloon as per institution protocol. What at first seemed a simple case suddenly turned into a series of cerebral and vascular complications that were successfully managed with a mix of peripheral, coronary and imaging techniques.